2004
DOI: 10.1002/eji.200424958
|View full text |Cite
|
Sign up to set email alerts
|

Diverse populations of T cells with NK cell receptors accumulate in the human intestine in health and in colorectal cancer

Abstract: T cells expressing NK cell receptors (NKR) display rapid MHC-unrestricted cytotoxicity and potent cytokine secretion and are thought to play roles in immunity against tumors. We have quantified and characterized NKR + T cells freshly isolated from epithelial and lamina propria layers of duodenum and colon from 16 individuals with no evidence of gastrointestinal disease and from tumor and uninvolved tissue from 19 patients with colorectal cancer. NKR + T cell subpopulations were differentially distributed in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 50 publications
5
94
1
3
Order By: Relevance
“…1B). Significant variation in CD56 ϩ T cell frequency was detected in the colon and small bowel (ranging 2-36 and 5-33%, respectively), in agreement with a study by Pittet et al (39), although lower frequency variations were reported in a second smaller cohort (16). Further analysis of colonic specimens from inflamed and uninvolved intestinal sites indicated reduced frequencies of CD56 ϩ T cells in inflamed sites ( p Ͻ 0.0001 vs non-IBD and p Ͻ 0.0028 vs uninvolved), whereas frequencies in uninvolved sites did not significantly differ from non-IBD mucosa (Fig.…”
Section: Cd56supporting
confidence: 91%
See 2 more Smart Citations
“…1B). Significant variation in CD56 ϩ T cell frequency was detected in the colon and small bowel (ranging 2-36 and 5-33%, respectively), in agreement with a study by Pittet et al (39), although lower frequency variations were reported in a second smaller cohort (16). Further analysis of colonic specimens from inflamed and uninvolved intestinal sites indicated reduced frequencies of CD56 ϩ T cells in inflamed sites ( p Ͻ 0.0001 vs non-IBD and p Ͻ 0.0028 vs uninvolved), whereas frequencies in uninvolved sites did not significantly differ from non-IBD mucosa (Fig.…”
Section: Cd56supporting
confidence: 91%
“…CD56 T cells were detected by surface immunostaining and flow cytometric analysis of lymphocytes isolated from the human intestinal LP (LP lymphocytes), MLNs, or peripheral blood (PB). Scatter plot analysis of gated live lymphocytes re- (16). CD56 staining intensity in CD3 ϩ T cell population was relatively low and almost exclusively corresponded to the CD56 dim profile, characteristic of a functionally distinct subset of NK cells (31), whereas CD3…”
Section: Cd56mentioning
confidence: 92%
See 1 more Smart Citation
“…Only a small minority of human CD161 ϩ T cells are NK T cells with the invariant TCR (V␣24V␤11), because the latter cells represent no less than 1% of all T cells in the lymphoid tissues and liver (12,13). Although, CD161 is expressed on the minority of human blood T cells, CD161 ϩ T cells expressing either CD4 or CD8 represented the majority of T cells from the epithelial and lamina propria layers of the human duodenum and colon (14). The latter cells contained few, if any, V␣24V␤11 invariant NK T cells and secreted IFN-␥ and TNF-␣ without IL-4 after in vitro stimulation.…”
Section: Expression Of Cd161 (Nkr-mentioning
confidence: 99%
“…[10][11][12] The frequency of these cells varies in certain pathologic conditions, such as cancer and viral or autoimmune diseases. [12][13][14][15] Recently, it has been demonstrated that a subset of naive cord blood CD4 T cells express CD161 and are precursors of peripheral, mature, Th17 T cells. 16 CD161 expression seems to correlate with interleukin-17 (IL-17) secretion by CD4 T cells.…”
Section: Introductionmentioning
confidence: 99%